Anxiety- and depression-related somatic symptoms and atlantoaxial disorders: potential mechanistic links and clinical implications - Shuxian Yang; Qianru Li; Wanying Shi; Xiaoyun Liu (Frontiers in Psychiatry, 2026)
Background Anxiety and depressive disorders often include pain, dizziness, headache, fatigue, nausea, and sleep disturbance. These symptoms may also occur in atlantoaxial disorders, but overlap does not establish a shared cause. Objective To examine whether clinical or mechanistic evidence supports an association between objectively defined atlantoaxial disorders and somatic symptom burden in people with anxiety or depression, while distinguishing direct evidence from inferences based on general neck-pain research. Methods PubMed/MEDLINE, Embase, Scopus, Web of Science Core Collection, and APA PsycInfo were searched from inception to 29 July 2026. Two complementary searches were conducted: the first combined atlantoaxial/C1–C2 conditions with anxiety, depression, or somatic-symptom concepts, and the second combined adjacent cervical conditions with the same psychiatric and somatic-symptom concepts. Evidence was classified as direct or partial-direct, adjacent, mechanistic inference, or hypothesis-generating. Because populations, diagnoses, and outcomes were heterogeneous, findings were synthesized narratively rather than pooled. Results The searches retrieved 8,882 records, of which 5,225 remained after deduplication. Only three studies provided partial-direct evidence by including both an upper-cervical variable and a psychiatric variable in the same population; two used imaging-based spinal assessments, whereas one relied on administrative diagnosis and procedure codes. None was designed to investigate somatic symptom disorder, none established that anxiety or depression caused structural C1–C2 disease, and none demonstrated a bidirectional causal relationship. General neck-pain studies support associations between psychological distress and pain-related outcomes, while studies of cervical dizziness and proprioception provide possible adjacent mechanisms. Autonomic, central pain-processing, inflammatory, sleep-related, and biomechanical pathways remain predominantly indirect or hypothetical in relation to atlantoaxial disease. Conclusions Atlantoaxial disorders and anxiety- or depression-related somatic symptoms may coexist and may have overlapping clinical presentations. Current evidence is insufficient to quantify a specific association or infer causality. Clinical assessment should prioritize neurological and vascular red flags, objective definition of C1–C2 pathology, clinicoradiological concordance, exclusion of common vestibular and neurological causes of dizziness, and parallel assessment of anxiety, depression, sleep disturbance, fear avoidance, and somatic symptom burden. Prospective studies using standardized imaging criteria and validated psychiatric measures are needed.